2010
DOI: 10.1124/jpet.110.165787
|View full text |Cite
|
Sign up to set email alerts
|

Terutroban, a Thromboxane/Prostaglandin Endoperoxide Receptor Antagonist, Increases Survival in Stroke-Prone Rats by Preventing Systemic Inflammation and Endothelial Dysfunction: Comparison with Aspirin and Rosuvastatin

Abstract: This study investigated the efficacy of terutroban, a specific thromboxane/prostaglandin endoperoxide receptor antagonist, on stroke incidence in spontaneously hypertensive strokeprone rats (SHRSP). The effects of terutroban were compared with those of aspirin, another antiplatelet agent, and rosuvastatin, known to exert end-organ protection in SHRSP. Saltloaded male SHRSP were treated orally once a day with vehicle, terutroban (30 mg/kg/day), aspirin (60 mg/kg/day), or rosuvastatin (10 mg/kg/day). Compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
(37 reference statements)
1
25
0
Order By: Relevance
“…Previously published data obtained in the same rat strain show that chronic terutroban treatment increases survival by reducing systemic inflammation and improving vascular reactivity in isolated carotid artery (11). The results of the present study show that chronic terutroban treatment also inhibits vascular hypertrophy and fibrosis in salt-loaded SHRSPs.…”
Section: Discussionsupporting
confidence: 73%
“…Previously published data obtained in the same rat strain show that chronic terutroban treatment increases survival by reducing systemic inflammation and improving vascular reactivity in isolated carotid artery (11). The results of the present study show that chronic terutroban treatment also inhibits vascular hypertrophy and fibrosis in salt-loaded SHRSPs.…”
Section: Discussionsupporting
confidence: 73%
“…We emphasize that in contrast to other authors, we did not apply a diet with 1% salt in drinking water (Lee et al, 2007;Gelosa et al, 2010). Therefore, in animals fed a salt-loaded diet, tissue infarctions occur in 80% of 30-week-old male SHRSP (Yamori and Horie, 1977;Tagami et al, 1987).…”
Section: Discussionmentioning
confidence: 96%
“…In animal studies, terutroban showed ability to reduce NOX upregulation and ROS production [60], improve endothelial function [36] and attenuate renal damage in hypertension [61]. In spontaneously hypertensive stroke-prone rats, the use of terutroban prevented cell proliferation in the vessel media, abolished accumulation of collagen and fibronectin in the vascular wall and inhibited expression of heat shock protein-47, MCP-1 and transforming growth factor 1β [62, 63]. …”
Section: Introductionmentioning
confidence: 99%